Effectiveness of the rehabilitative treatment in women with postmastectomy lymphedema - Mayda Bárbara Herrera Santos; Leydys Magda Valenzuela Fonseca; Joel Herrera Bravo (Centro Provincial de Información de Ciencias Médicas, 2017)
A therapeutic intervention study was carried out in 20 women aged 40-85 with postmastectomy lymphedema, assisted in the rehabilitation services of "Ramón López Peña" and "Armando García Aspurú" teaching polyclinics in Santiago de Cuba from August, 2012 to September, 2013, aimed at evaluating the effectiveness of the rehabilitative treatment, for which rehabilitative techniques of lymphatic drainage, kinesitherapy, occupational therapy were used and evolutive evaluations with pain scales, muscular strength, articular movement and functionality were carried out. It was concluded that 90% of the patients aged 40-59, with less than 6 months of clinical course, had better results at the end of the study, so the treatment was effective.